2016
DOI: 10.3389/fpsyt.2016.00001
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Non-Theta-Contingent Eyeblink Classical Conditioning: A Model System for Neurobiological Dysfunction

Abstract: Typical information processing is thought to depend on the integrity of neurobiological oscillations that may underlie coordination and timing of cells and assemblies within and between structures. The 3–7 Hz bandwidth of hippocampal theta rhythm is associated with cognitive processes essential to learning and depends on the integrity of cholinergic, GABAergic, and glutamatergic forebrain systems. Since several significant psychiatric disorders appear to result from dysfunction of medial temporal lobe (MTL) ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
84
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 203 publications
(224 reference statements)
9
84
0
Order By: Relevance
“…This would suggest that there has been a collapse of the top-down modulatory networks controlling gating more generally. As such, the present neurophysiological analysis is consistent with that of our recent fMRI network analysis (Thoma et al, 2016), the results of which suggested that as one moves into the AVH-on state, pre-frontally mediated networks, presumably associated with executive control, go off-line, and a predominant temporal lobe AVH network emerges supporting the experience of AVH.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This would suggest that there has been a collapse of the top-down modulatory networks controlling gating more generally. As such, the present neurophysiological analysis is consistent with that of our recent fMRI network analysis (Thoma et al, 2016), the results of which suggested that as one moves into the AVH-on state, pre-frontally mediated networks, presumably associated with executive control, go off-line, and a predominant temporal lobe AVH network emerges supporting the experience of AVH.…”
Section: Discussionsupporting
confidence: 91%
“…Questions regarding the extent to which patients are able to successfully indicate the onset or offset of AVH may bear on the present conclusions, but data presented elsewhere demonstrated a high test-retest reliability of our button press protocol in an overlapping sample of schizophrenia patients (Thoma et al, 2016). Lastly, these findings emphasize the importance of using the temporal sensitivity of neurophysiological measures to better understand the state-related changes in neural functioning underlying schizophrenia symptoms.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Within a project on biological consequences of childhood experiences and trauma, a subsample of former child laborers provided further information (Küffer et al, 2016). Data collection for the parental control sample was done within the context of the current study between 2013 and 2014.…”
Section: Methodsmentioning
confidence: 99%
“…6 7 These differences affect MDD in terms of the factors involved in the development and maintenance of MDD, the way in which MDD symptoms are manifested, and how MDD is expressed, discussed and managed. [8][9][10][11][12][13][14][15][16] Studies have also found that culture influences physical health and medical conditions. 17 18 In terms of reporting the symptoms of MDD, Chinese and Malaysian Chinese patients tend to focus on the somatic symptoms, while patients from American, European Canadian and European Australian cultural backgrounds tend to focus on the psychological symptoms.…”
Section: Introductionmentioning
confidence: 99%